La convivencia multicultural y la función de los cuentos infantiles para conseguirla - Calvo Gómez-Rodulfo, María José (Magister, 2005)
Tales for Children are didactic means with a great educational utility. They talk about human¿s esential necessities, so they are valid for every culture. Popular knowledge creates or keeps them, and with them transmits to its new members, behaviour patterns with which they can reach success, avoid failure and achieve happiness. Children live them with great emotional intensity; this fact assures they¿ll survive for a long time in his memory. Nota: este documento forma parte de la colección de revistas de la Biblioteca Universitaria (Universidad de Oviedo). Le rogamos que se ponga en contacto con su biblioteca de centro para comprobar la disponibilidad y gestionar la obtención del documento original o una copia del mismo.